(untitled) (Comunicação & Inovação, 2020)
In this article, we address the interface between Communication and Health, focusing on the "biopolitical convocations" (Prado, 2013) in Nike’s and Pão de Açúcar’s advertising in the Covid-19 pandemic, as well as the displacement of a "classic" biopolitics ( Foucault, 1988) - aimed at the government of populations - for a "biopolitics of consumption", characterized by self-care and self-management. Therefore, the theoretical framework that underlies our reflections mobilizes authors dedicated to the studies of consumption, communication, health and biopolitics